2017
DOI: 10.1101/189654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput identification of RNA nuclear enrichment sequences

Abstract: Summary 27One of the biggest surprises since the sequencing of the human genome has been the discovery 28 of thousands of long noncoding RNAs (lncRNAs) [1][2][3][4][5][6] . Although lncRNAs and mRNAs are similar 29 in many ways, they differ with lncRNAs being more nuclear-enriched and in several cases 30 exclusively nuclear 7,8 . Yet, the RNA-based sequences that determine nuclear localization remain 31 poorly understood [9][10][11] . Towards the goal of systematically dissecting the lncRNA sequences that 32 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…Retention of MALAT1 in speckles depends on two distinct sequence elements, which are also involved in binding to the nuclear speckle enriched protein RNPS1 (Figure ; Miyagawa et al, ). Consistently, these regions were identified in a recent high‐throughput screen for RNA sequence elements that promote nuclear retention (Shukla et al, ).…”
Section: Main Bodymentioning
confidence: 56%
See 2 more Smart Citations
“…Retention of MALAT1 in speckles depends on two distinct sequence elements, which are also involved in binding to the nuclear speckle enriched protein RNPS1 (Figure ; Miyagawa et al, ). Consistently, these regions were identified in a recent high‐throughput screen for RNA sequence elements that promote nuclear retention (Shukla et al, ).…”
Section: Main Bodymentioning
confidence: 56%
“…The Massively Parallel RNA assay (MPRNA) by Shukla et al () took advantage of the sequences of 37 lncRNAs, with known localizations in both nuclear and cytoplasmic compartments, to generate approximately 12,000 overlapping barcoded oligonucleotides. These sequences were then fused to reporter constructs, known for their native cytoplasmic localizations, and transfected into HeLa cells before sequencing either nuclear or total cellular RNA (Shukla et al, ). Approximately 110 unique RNA tags were identified, that showed a significant relative enrichment in the nuclear fraction.…”
Section: Main Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Two new studies now use elegant tiling‐based approaches to screen for cis ‐acting RNA elements involved in nuclear retention. The first study (Shukla et al , ) developed Massively Parallel RNA Assay (MPRNA) that is based on sequences from 38 human lncRNAs, which were chosen to cover a spectrum of nuclear and cytosolic localization patterns. Briefly, 11.969 unique, barcoded oligos of 153 nt length were designed to tile the lncRNA sequences in a partially overlapping manner (Fig ).…”
Section: High‐throughput Screening Approaches Using Oligos Allow the mentioning
confidence: 99%
“…The study by Lubelsky and Ulitsky () found that both the presence of SIRLOIN motifs and the presence of hnRNPK binding sites correlate with nuclear enrichment of lncRNAs and mRNAs. Shukla et al () performed a comparative analysis of ENCODE RNA‐seq data produced from nuclear and cytoplasmic fractions of 11 cell lines and similarly found a correlation of DRs with nuclear retention, with the effect being more pronounced for lncRNAs than mRNAs. Interestingly, the RNAs that are strictly nuclear tend to have many repeats of DRs; for example, 18 DRs are present in XIST and 10 in MALAT1 lncRNAs.…”
Section: High‐throughput Screening Approaches Using Oligos Allow the mentioning
confidence: 99%